New forces at work : industry views critical technologies - Popper, Steven W., 1953-; Wagner, Caroline S.; Larson, Eric V. (Eric Victor), 1957-; Rand Corporation; United States. Office of Science and Technology Policy; Critical Technologies Institute (Rand Corporation) (Santa Monica, CA : Rand, 1998)
For the fourth in a series of inquiries into the state of critical technologies in the United States, the Office of Science and Technology Policy in the Executive Office of the President asked a RAND Critical Technologies Institute research team to engage business and industry leaders explicitly in a discussion of the issue of critical technologies by gathering private-sector views on what technologies are appropriate to consider under this rubric--and why. The primary substantive input was elicited through extended, detailed interviews conducted individually, usually with one firm's senior executive per session, on-site in most cases. This report presents an analysis of the information gained during the course of those interviews. The report presents and analyzes interviewees' responses to what technologies they consider to be critical to their firm or industry; explores the question of what "critical technology" means; reports interviewees' assessments of the status of U.S.
Efforts and performance in the areas of technology they deemed critical; considers the respective roles of industry, universities, and government in contributing to and sustaining the U.S. technology base; suggests a process whereby the dialogue between government and industry on the public policy issues relating to technology might be made more integral and informative to the activities of both. The responses of many of the interviewees emphasized the aspect of technology as process over technology as product. In line with this vision, the authors propose a critical-technologies review process that would enable wider, more meaningful, and ongoing communication among industry, government, and universities on technology issues. The research reported here should be of interest to government policymakers concerned with a wide range of issues touching on U.S.
Technology performance, to members of industry and the academic community who follow issues of technology in general or concentrate on specific areas, and to members of the public who have an interest in the public policy of science and technology in this country.
Introduction: Toward a New View of Critical Technologies -- Part I -- What Are the Critical Technologies? Ch. 1. Critical Technologies of Today. Ch. 2. Over the Horizon: Technologies in Evolution and Revolution. Ch. 3. Technologies of National Importance -- Part II -- Critical Technologies in the Larger Context. Ch. 4. The Sources of Critical Technology. Ch. 5. Government's Role in Fostering Critical Technologies -- Part III -- New Paths for Assessing Critical Technologies. Ch. 6. Recasting Discussion of Critical Technologies -- A. The Interviews -- B. List and Frequency Check of Critical Technologies.
"This report was conducted by Rand's Critical Technologies Institute under Contract OPA-9215205."
"Supported by the Office of Science and Technology Policy."
"Critical Technologies Institute."
Includes bibliographical references (pages 149-155).
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
Keywords: Technology assessment -- United States; Technologie -- Évaluation -- États-Unis.; POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Structural Adjustment; BUSINESS & ECONOMICS -- Development -- General; Technology assessment; United States; Neue Technologie; Technikbewertung; USA; Technology - General; Engineering & Applied Sciences